The Scope and Prospects of Photoelectrochemistry for C-H Bond Activation Using Semiconductor Photoanodes - Gupta H.; Saunkhla R.; Indra A. (My University, 2025)
The high activation energy needed for C-H bond activation leads to the requirement for harsh reaction conditions, specially designed catalysts, additives, and terminal oxidants. Tremendous progress has been achieved in C-H bond activation using thermocatalysis, photoredox, electrocatalysis, and electrophotocatalysis methods. Recently, photoelectrochemistry using semiconductor photoanodes has been explored for C-H bond activation, and the approach has certain advantages and challenges. The use of both light and applied potential makes C-H bond activation facile compared to the electrochemical or photoredox reactions. Further, high atom economy, low side product and waste formation, mild reaction conditions, and high energy efficiency associated with photoelectrochemistry make it more convenient than the other processes. However, the design of effective photoanodes using a suitable choice of semiconductor and cocatalyst is crucial for improving the charge-transfer dynamics, reaction rates, and selectivity for the desired products. Although the field is relatively new, a significant number of studies have demonstrated its versatility and robustness for different types of C-H bond activation. Herein, we describe the scope of photoelectrochemistry for C-H bond activation and discuss its future and potential for large-scale organic synthesis. 1 Introduction 2 Types of C-H Activation 3 Importance of Photoelectrochemical Approaches 4 Improvement of the Activity 5 Control over the Selectivity 6 Photoanode Design 7 The Effect of Cocatalysts 8 The Effect of Charge Collectors 9 The Effect of Redox Mediators 10 Conclusions and Perspectives © 2025. Thieme. All rights reserved.